Nurses' perceptions of open disclosure processes in cancer care: a cross-sectional study. Issue 5 (October 2020) - Waller, Amy; Hobden, Bree; Bryant, Jamie; Shepherd, Jan; Turon, Heidi; Sanson-Fisher, Rob
Abstract: Background: Despite their central role in patient care, few studies have explored cancer nurses' perspectives about errors within the health care system. Aims: To determine in a sample of cancer nurses the: (1) perceived accuracy of patient-reported health care error rates in medical oncology and haematology care; (2) extent to which nurses' perceive the health care system responds to errors in accord with best-practice disclosure standards; and (3) association between perceived barriers to disclosure of errors and years of experience, number of errors in previous six months and nursing role. Methods: Cross-sectional online survey of members of an oncology nursing society and/or registered or enrolled nurses employed in an oncology setting. Descriptive statistics including frequencies and proportions were calculated for all variables, and chi-square/Fisher's exact test was used to explore the association between perceived barriers to disclosure and several predictor variables. Findings: Ninety-seven nurses across the two cohorts completed the survey. Across the two cohorts, 36% and 27% of nurses perceived medical oncology and haematology patient-reported error rates to be accurate, respectively. Sixty-six percent agreed data should be routinely collected from patients; and 90% agreed data should be reported back to treatment centres. Nurses perceived patients were 'always': given an apology (24%); able to ask questions (20%), told steps taken to prevent future errors (18%), told about errors when they happened (16%) and given honest explanations (17%). Barriers to error disclosure included burden of reporting (75%), fear career damage (74%), lack institutional support (65%), fear legal action (64%), no patient harm (58%) and not nurses' responsibility (27%). Discussion: Nurses did not consistently agree that previously-reported patient-reported error rates were accurate. Nurses agreed patient-reported data on health care error rates should be collected and fed back to treatment centres and that there is room for improvement with regard to adherence to open disclosure standards. Conclusion: System-level strategies are required to overcome barriers to disclosure.